Baseline assessment of the reef fish assemblage from Cagarras Archipelago, Rio de Janeiro, southeastern Brazil (Brazilian Journal of Oceanography, 2007)
The extensive Brazilian coast comprises diverse reef fish communities. Here, we report a pioneer study on the reef fish community composition of the Cagarras Archipelago. This rocky reef system consists of a small group of coastal islands 5 km south off Ipanema Beach, Rio de Janeiro city, Brazil. A relatively diverse and disturbed fish community (99 species from 39 families) was found in this archipelago. Two different visual census techniques were utilized and a large difference was observed in the number of species compared to other Brazilian reef sites. Trophic structure and biogeographical affinities are discussed. The absence of some reef fish species, mainly top predators, suggests severe environmental impact in this area and exhorts the Brazilian authorities to create a marine protected area. Results obtained in this study will serve to future environmental studies in Cagarras.